Neurological Emergencies in Refugees - Brinckmann, Marie P.; van Noort, Betteke M.; Leithner, Christoph; Ploner, Christoph J. (Frontiers in Neurology, 2018)
Objective: Health care personnel in Europe is increasingly involved in care of displaced persons from non-European countries; we investigated the spectrum of neurological disorders and medical management in refugees presenting to the emergency room (ER) of a German university hospital. Methods: We retrospectively studied ER-patients with refugee status (R-patients) during the peak of the European refugee crisis between July 2015 and February 2016 (N = 100). Complaints on admission, medical management and diagnoses at discharge were compared to matched groups of German residents with migrational background (M-patients; N = 96) and to native Germans (N-patients; N = 95). Results: R-patients were mostly male young adults (75% male; mean age 33.2 years). Headache was the most frequent complaint in all groups (R-patients 38%; M-patients 43%; N-patients 24%). R-patients, however, presented much more often with possible or definite seizures (R-patients 27%; M-patients 9%; N-patients 15%). Initial triage, length of medical history and examination records, utilization of laboratory tests and cranial imaging did not differ between groups. However, time to diagnosis was considerably longer in R-patients (220 min; M-patients 151 min, N-patients 123 min). While strokes and other life-threatening emergencies were rare final diagnoses in R-patients, a substantial proportion was discharged with a diagnosis of non-epileptic seizures or a psychiatric disorder (20%; M-patients 6%; N-patients 7%). Conclusions: Refugee patients present with a spectrum of neurological disorders that not solely results from cultural differences but rather reflects the consequences of forced displacement. ER management of refugees requires more time, language skills and critically depends on psychosomatic/psychiatric expertise.